Respuesta :

Answer:

[tex](x-3)^2=8(y+1)[/tex]

Step-by-step explanation:

Standard form of a parabola with a vertical axis of symmetry:

[tex](x-h)^2=4p(y-k) \quad \textsf{where}\:p\neq 0[/tex]

[tex]\textsf{Vertex}=(h, k)[/tex]

[tex]\textsf{Focus}=(h,k+p)[/tex]

[tex]\textsf{Directrix}:y=(k-p)[/tex]

[tex]\textsf{Axis of symmetry}:h=k[/tex]

If p > 0, the parabola opens upwards, and if p < 0, the parabola opens downwards.

From inspection of the graph:

  • Vertex = (3, -1)
  • Directrix = y = -3

Therefore:

  • h = 3
  • k = -1
  • k - p = -3

Use the Directrix equation to find p

⇒ y = (k - p)

⇒ -3 = -1 - p

⇒ p = 2

Therefore the equation of the conic section is:

[tex]\implies (x-3)^2=4\cdot 2(y-(-1))[/tex]

[tex]\implies (x-3)^2=8(y+1)[/tex]

Rearranging in standard form [tex]ax^2+bx+c[/tex]:

[tex]\implies (x-3)^2=8y+8[/tex]

[tex]\implies x^2-6x+9-8=8y[/tex]

[tex]\implies x^2-6x+1=8y[/tex]

[tex]\implies y=\dfrac{1}{8}x^2-\dfrac{3}{4}x+\dfrac{1}{8}[/tex]

ACCESS MORE